Democratization of Political Parties in Nepal: Impact on Strengthening the Constitution - Timilsina, Krishna Prasad (INTELLIGENCE Journal of Multidisciplinary Research, 2026)
Democracy is a widely accepted system of government. Consolidated institutions and honest behavior are the primary requirements for the successful working of this system. Hence, this article aims to make a critical analysis of the democratization of political parties in Nepal, and impact on strengthening the constitution. Despite three-quarters of a century (almost 75 years) of democratic practice of political parties, Nepal has a bitter experience of fragile democracy. The study concludes that the political party in a democratic system requires a consolidated institution and actors’ normative commitment towards the system. Political parties are central to democracy, which serves as agents of political change, representation, and governance. This article examines the contributions and limitations of different political parties in Nepal in institutionalizing political change at various times, the constitutional provisions, and the problems that arise in the practical implementation of their democratic conduct. Since political parties are agents of change and a synonym for democracy, this article focuses on assessing their democratic condition. This article attempts to identify the bases for the democratization of Nepal's political parties, constitutional provisions, and parties. Using secondary sources and qualitative analysis, this study identifies challenges, including leadership entrenchment, lack of financial transparency, and limited inclusiveness within party structures. The findings of this study clarify how Nepal’s political parties played pivotal roles in democratic movements and constitution-making; however, their internal democratization remains incomplete. Strengthening constitutional compliance, ensuring inclusivity, and promoting transparent party practices are essential for consolidating democracy in Nepal. This study contributes to understanding party institutionalization in post-conflict democracies and offers practical insights for political reformers and policymakers.